RESEARCH OF CHARACTERISTICS OF PROCESS NEUTRALIZATION OF ACID WASTEWATER BY LIME SLUDGE - Sabina Begić; Vladan Mićić; Zoran Petrović; Selma Tuzlak (Journal of Engineering & Processing Management, 2014)
Lime sludge which is generated in the industrial processes of water softening is a significant environmental and economic burden, due to increasingly stringent of national and international regulations relating to the management of waste streams. The high content of calcium carbonate in this material opens the possibility of its application in the processes of acidic waste water neutralization. In this paper, a research of characteristics of the process of neutralizing the acidity of water in terms of different initial pH value and flow regime, applying lime sludges which are generated in treatment of salt and fresh water, was conducted. Results of research showed that the initial pH value of water and the presence of NaCl have a significant effect on the solubility of calcium carbonate in the process of neutralization, while the examined flow regime (mixing speed of magnetic stirrer) had a negligible impact.
Keywords: lime sludge; acid water neutralization; calcium carbonate